2018
DOI: 10.1021/jacs.8b01510
|View full text |Cite
|
Sign up to set email alerts
|

Bromide as a Robust Backfiller on Gold for Precise Control of DNA Conformation and High Stability of Spherical Nucleic Acids

Abstract: Functionalization of a gold surface with DNA is often complicated by kinetic traps from unintended DNA base adsorption. Herein, we communicate that Br serves as a robust backfilling agent displacing selected DNA bases on gold. Traditional thiol backfillers are too strong, while even 300 mM Br is well tolerated. Conjugates prepared with Br hybridize 10-fold faster and resist DNA release with better colloidal stability yielding highly sensitive probes. From colorimetric and Raman assays, adsorption affinity rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 52 publications
(17 reference statements)
2
118
0
Order By: Relevance
“…In addition, DNA adsorption is also promoted at low pH (Zhang et al, 2012b) and by freezing (Liu and Liu, 2017a). We also noticed the effect of various anions such as bromide (Liu et al, 2018b), and arsenate (Zong et al, 2019), and small molecules (Wu et al, 2019), which compete with DNA for the adsorption sites on gold.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, DNA adsorption is also promoted at low pH (Zhang et al, 2012b) and by freezing (Liu and Liu, 2017a). We also noticed the effect of various anions such as bromide (Liu et al, 2018b), and arsenate (Zong et al, 2019), and small molecules (Wu et al, 2019), which compete with DNA for the adsorption sites on gold.…”
Section: Introductionmentioning
confidence: 66%
“…DNA-functionalized gold nanoparticles (AuNPs) (Brewer et al, 2005;Giljohann et al, 2007;Patel et al, 2011;Cutler et al, 2012;Pei et al, 2012;Xiang et al, 2013;Wang et al, 2017;Liu and Liu, 2019) have been extensively studied in terms of preparing the conjugate (Liu and Liu, 2017b), sensing (Wu et al, 2018), making materials (Tan et al, 2014;Jones et al, 2015), and cell-related applications (Giljohann et al, 2010). All the four DNA bases can strongly adsorb on gold via coordination interactions (Liu et al, 2018b), and thus even non-thiolated DNA can be attached to AuNPs (Kimura-Suda et al, 2003;Pei et al, 2012;Zhang et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al 48 reported on the use of bromide ion (Br -) as a backfiller in order to obtain better control of the ssDNA conformation on a gold substrate. The affinities of Brand four nucleosides are as follows: T < C < G ≈ Br -< A, and Brcould make the immobilized aptamer stay an upright conformation.…”
Section: Aptamer Immobilization In Nabr Solutionmentioning
confidence: 99%
“…The interaction and hybrids between DNA and nanomaterials have received extensive and increased research interest in the past decade. [1][2][3] Among them, carbon nanomaterials for DNA adsorption or attachment are promising and effective tools for biosensing, material design, gene delivery, and in vivo responsive drug system. 4,5 The surface attachment of DNA on carbon nanomaterials via some clear interactive forces is the key role in the application of DNA and nanomaterial hybrids.…”
Section: Introductionmentioning
confidence: 99%